2017
DOI: 10.3892/mmr.2017.6568
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of PARP-1 exert inhibitory effects on the biological characteristics of hepatocellular carcinoma cells in vitro

Abstract: It has been confirmed that the inhibitors of poly ADP-ribose polymerF(^9ase-1 (PARP-1) can inhibit the proliferation, apoptosis and invasion of tumor cells. However, the effects of inhibitors of PARP-1 on hepatocellular carcinoma remain to be elucidated. The aim of the present study was to investigate the effect of three types of PARP-1 inhibitor on the proliferation, apoptosis and migration of hepatocellular carcinoma in vitro. An MTT assay was performed to detect the proliferation of HepG2 cells following tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This is supported by a number of in vitro and in vivo studies, which have demonstrated pro-tumourigenic effects of PARP1 in HCC including increased proliferation, growth, angiogenesis, invasion and metastatic gene mRNA upregulation [64,68]. Supporting this, a number of in vitro studies in HCC have demonstrated that PARP inhibition results in an increase in apoptosis via the mitochondrial pathway [68,69]. However, Radnai et al, demonstrated an opposing effect with PARPi treatment inhibiting HCC apoptosis, an effect similarly observed in premalignant alcoholic liver disease [70,71].…”
Section: Hepatic Cancermentioning
confidence: 84%
“…This is supported by a number of in vitro and in vivo studies, which have demonstrated pro-tumourigenic effects of PARP1 in HCC including increased proliferation, growth, angiogenesis, invasion and metastatic gene mRNA upregulation [64,68]. Supporting this, a number of in vitro studies in HCC have demonstrated that PARP inhibition results in an increase in apoptosis via the mitochondrial pathway [68,69]. However, Radnai et al, demonstrated an opposing effect with PARPi treatment inhibiting HCC apoptosis, an effect similarly observed in premalignant alcoholic liver disease [70,71].…”
Section: Hepatic Cancermentioning
confidence: 84%
“…Indeed, Fehling et al highlighted a synergistic action of BET inhibitors (JQ1) with PARPi in CCA cell lines [102]. Another pre-clinical study suggested a potential role of olaparib in sensitizing CCA cells to radiation [103], as reported above for CRC. Moving from the benchside to the bedside, clinical trials are currently ongoing.…”
Section: Cholangiocarcinoma and Hepatocellular Carcinomamentioning
confidence: 85%
“…In our results, the dinaciclib and alvocidib interacted with the CDK1 . The rucaparib (AG014699), which was the inhibitor of the poly (ADP-ribose) polymerase-1 (PARP-1), might induce the apoptosis of HepG2 cells through the mitochondrial pathway and induced the migration of HepG2 cells by upregulating the PTEN and increasing the TIMP-3/MMP-3 ratio [ 90 ]. The traditional chemotherapeutic drugs (epirubicin, cyclophosphmide, and fluorouracil) played the important roles in treatment of liver cancer [ 91 ].…”
Section: Discussionmentioning
confidence: 99%